STRATEGI GURU PAI DALAM MENYELENGGARAKAN PEMBELAJARAN AGAMA ISLAM PADA ERA NEW NORMAL DI SMA NEGERI 5 MALANG - Karmila Sari; Nur Hasan; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
In the strategy applied by educational institutions, empowerment is one way that is carried out by a process of giving proportional authority and responbility. Creating conditions of trust and involving teachers in completing tasks and making decisions. There is a focus research discussing the steps of the implementation process and the obstacles faced by PAI teachers in implementing Islamic religious learning strategies in the new normal era, the aim of this research is to use a phenomenological-based qualitative approach using case study research. The media determines the method of determining the teching materials and determining the material. The implementation of this research uses face-to-face and remote implantation. The obstacles to the law research are the lack of involvement og SIGNA, the inequality of students in accessing the media, learning that is limited by time. Kata Kunci: PAI Teacher Strategy, Islamic Religious Learning, New Normal.